The Shawshank redemption - Robbins, Tim, 1958-; Freeman, Morgan; Gunton, Bob.; Sadler, William, 1950-; Brown, Clancy; Bellows, Gil.; Whitmore, James; Darabont, Frank; King, Stephen, 1947-; Castle Rock Entertainment (Firm) (Burbank, CA : Warner Home Video, 1999)
Two convicts, one white and one black, never give up the dream of freedom, and together they turn hope and friendship into an uplifting bond no prison can ever take away.
Also contains a stills gallery, interactive menus, a theatrical trailer and provides scene access.
Based on the short novel "Rita Hayworth and Shawshank Redemption" by Stephen King.
Originally produced as motion picture in 1994.
Screenplay, Frank Darabont ; producer, Niki Marvin ; director, Frank Darabont.
Tim Robbins, Morgan Freeman, Bob Gunton, William Sadler, Clancy Brown, Gil Bellows, James Whitmore.
MPAA rating: R.
Keywords: Prisons -- Drama; Feature films